The Irish regiments in the Great War : discipline and morale - Bowman, Timothy (Manchester ; New York : Manchester University Press ; New York : Distributed exclusively in the USA by Palgrave, 2003)
A comprehensive study of discipline and morale in the British army during the Great War, using the Irish regiments as a case study. The book suggests that, while minor breaches of discipline did occur in the Irish regiments, executions took place out of the need to restore military discipline.
Measuring discipline and morale -- Regular regiments at war -- Raising the Service battalions -- Adjusting and adapting -- Amalgamations, reductions and conscription -- The final phase -- Irish units on Home Service -- Conclusion.
Includes bibliographical references (pages 210-224) and index.
English.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Great Britain. -- Army -- Irish regiments -- History; Grande-Bretagne. -- Army -- Régiments irlandais -- Histoire; Great Britain. -- Army; World War, 1914-1918 -- Regimental histories -- Great Britain; World War, 1914-1918 -- Regimental histories -- Ireland; Guerre mondiale, 1914-1918 -- Histoire des unités -- Grande-Bretagne.; Guerre mondiale, 1914-1918 -- Histoire des unités -- Irlande; Humanities; History; Military history; First World War; HISTORY -- Military -- World War I; HISTORY -- Europe -- Great Britain; Regimental histories; Ireland; Great Britain; Weltkrieg; Großbritannien; Regiment; Regimenten; Moraal; Discipline; Eerste Wereldoorlog; Guerre mondiale (1914-1918) -- Grande-Bretagne.; Guerre mondiale (1914-1918) -- Participation irlandaise; Guerre mondiale (1914-1918) -- Histoire des unités -- Irlande; Guerre mondiale (1914-1918) -- Histoire des unités -- Grande-Bretagne.; Iren; 1914-1918; Multi-User.; Electronic books; History